Prevalence and function of Heschl’s gyrus morphotypes in musicians - Benner, Jan; Wengenroth, Martina; Schneider, Peter (Brain structure & function, 2017)
Morphological variations of the first transverse Heschl’s gyrus (HG) in the human auditory cortex (AC) are common, yet little is known about their functional implication. We investigated individual morphology and function of HG variations in the AC of 41 musicians, using structural and functional magnetic resonance imaging (fMRI) as well as magnetoencephalography (MEG). Four main morphotypes of HG were (i) single HG, (ii) common stem duplication (CSD), (iii) complete posterior duplication (CPD), and (iv) multiple duplications (MD). The vast majority of musicians (90%) exhibited HG multiplications (type ii-iv) in either one (39%) or both (51%) hemispheres. In 27% of musicians, MD with up to four gyri were found. To probe the functional contribution of HG multiplications to auditory processing we performed fMRI and MEG with auditory stimulation using analogous instrumental tone paradigms. Both methods pointed to the recruitment of all parts of HG during auditory stimulation, including multiplications if present. FMRI activations extended with the degree of HG gyrification. MEG source waveform patterns were distinct for the different types of HG: (i) hemispheres with single HG and (ii) CSD exhibited dominant N1 responses, whereas hemispheres with (iii) CPD and (iv) MD exhibited dominant P1 responses. N1 dipole amplitudes correlated with the localization of the first complete Heschl’s sulcus (cHS), designating the most posterior anatomical border of HG. P2 amplitudes were significantly higher in professional as compared to amateur musicians. The results suggest that HG multiplications occur much more frequently in musicians than in the general population and constitute a functional unit with HG.